Privatizing disability insurance - Arthur Seibold; Sebastian Seitz; Sebastian Siegloch (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Public disability insurance (DI) programs in many countries face pressure to reduce their generosity in order to remain sustainable. In this paper, we investigate the welfare effects of giving a larger role to private insurance markets in the face of public DI cuts. Exploiting a unique reform that abolished one part of the German public DI system for younger cohorts, we find that despite significant crowding-in effects, overall private DI take-up remains modest. Private DI tends to be concentrated among high-income, high-education and low-risk individuals. We do not find any evidence of adverse selection on unpriced risk. Finally, we estimate individual insurance valuations via a revealed preferences approach, a key input for welfare calculations. We find that observed willingness-to-pay of many individuals is low, such that providing coverage partly via a private DI market improves welfare. However, we show that distributional concerns as well as individual risk misperceptions can provide grounds for justifying a full public DI mandate.
Keywords: H55; G22; G52; 330; disability insurance; privatization; welfare; microdata